Influence of gear loss factor on the power loss prediction - Carlos M C G Fernandes (2015)
In order to accurately predict the power loss generated by a meshing gear pair the gear loss factor must be properly evaluated. Several gear loss factor formulations were compared, including the author's approach. A gear loss factor calculated considering the load distribution along the path of contact was implemented. The importance of the gear loss factor in the power loss predictions was put in evidence comparing the predictions with experimental results. It was concluded that the gear loss factor is a decisive factor to accurately predict the power loss. Different formulations proposed in the literature were compared and it was shown that only few were able to yield satisfactory correlations with experimental results. The method suggested by the authors was the one that promoted the most accurate predictions.